Applications on Ultrasonic Wave - Lee, Jaesun (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book presents applications on the ultrasonic wave for material characterization and nondestructive evaluations. It could be of interest to the researchers and students who are studying on the fields of ultrasonic waves.